Negative Energy Balance dan Days Open Pada Berbagai Tingkat Paritas Partus Sapi Fries Holland - Bambang Hadisutanto; Hermilinda Parera (JURNAL KAJIAN VETERINER, 2019)
Negative Energy Balance is a transition period that is transitional between 3 weeks before parturition until 3 weeks after parturition. Days open is the interval between calving parturition with marriage that produced approximately 85 days of gestation. Parity is a period in the reproductive cycle of cattle with an indication of the number of livestock parent parturition. The purpose of research is to find out the negative energy balance and open days at various parity cows parturition Fries Holland.This study design was used to observe the one-way classification parent dairy cows after parturition I, II and III respectively as many as 30 individuals. Data observation glucose levels and days open were analyzed by the General Linear Model (GLM) and followed by DMRT to determine the significance level of blood glucose levels and days open between parity parturition.The results showed that the blood glucose levels of 30 breeding dairy cows at parturition turns holding each parity parity I showed significant differences (51.57 ± 5.56 mg / dL) compared to the parent parity II (45.57 ± 8.01 mg / dL) and parent parity III (46.7 ± 8.62 mg / dL). While holding Open Days parity I (106.07 ± 38.11 days) showed a longer time than the days of open parent parity II (86.23 ± 29.00 days) and III (89.23 ± 38.22 days).The conclusion of this study is negative energy balance which were carried in the blood glucose levels are still within the normal range is 33-55 mg / dL. While holding open days longer than the first parity with the parent parity II and III.